PENGARUH PELATIHAN SPEED, AGILITY, QUICKNESS (SAQ) TERHADAP KECEPATAN REAKSI PENJAGA GAWANG SEPAKBOLA - Apriliyanto, Rizki (UNIVERSITAS NEGERI MAKASSAR, 2020)
The purpose of the study was to examine the effect of speed, agility, and quickness training on the reaction speed of the soccer goalkeeper. There are two groups, namely the experimental group with speed, agility, and quickness training and the control group with conventional training. The method used is experimental research using a randomized control group pretest-posttest design. The analysis technique uses a dependent paired t-test. Different test results can be seen that the t-value calculated in the experimental group 9787, the control group with a value of 1.990. influence is obtained from the value of p = 0.000 <0.05, which means that the training methods of speed, agility, and quickness can increase the reaction speed of the soccer goalkeeper. Football goalkeeping coach recommendations in increasing reaction speed in order to provide speed, agility and quickness training.